Postoperative assessment of diode laser zinc oxide eugenol and mineral trioxide aggregate pulpotomy procedures in children: A comparative clinical study - Bang Pratima; G D Chandan; Talreja Nidhi; Ingale Nitish; Murthy Sankriti; Sangavi Nagaveni; Saraf Shweta (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2018)
Aim: The present study is an attempt to compare and evaluate postoperative assessment of diode laser zinc oxide eugenol (ZOE) pulpotomy and diode laser mineral trioxide aggregate (MTA) pulpotomy procedures in children. Materials and Methods: Forty carious primary molars indicated for pulpotomy within the age group of 4–9 years were selected and divided into two groups of 20 each using simple randomization, Group 1: Diode laser MTA and Group 2: Diode laser ZOE pulpotomy. The teeth were evaluated clinically for 1 year at 3, 6, and 12 months interval and radiologically for 6 and 12 months. Results: Clinically and radiographically, 100% teeth treated with diode laser MTA and 94% treated with diode laser ZOE were considered successful after 12-month follow-up interval. No significant difference was seen between two groups. Conclusion: Despite the success rate, the cost factor of diode laser and MTA could be the limiting factor in its judicious use in pulpotomy procedure.